2016
DOI: 10.1080/02701960.2016.1230738
|View full text |Cite
|
Sign up to set email alerts
|

Integrating gerontological competencies in Canadian health and social service education: An overview of trends, enablers, and challenges

Abstract: As the number of older adults increases, it is imperative that gerontological competencies are imbedded in health and social service education reviews of Canadian published and grey literature presents trends, barriers, and enablers of sustained movement toward graduating professionals with gerontology competencies. Overall, gerontological education remains insufficient. Main barriers include resources for faculty and teaching. This review also identified discipline-specific competency frameworks that could in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 32 publications
0
23
0
Order By: Relevance
“…Nursing Service" in their spare time, thereby enhancing their personal value. [5][6][7] Nursing students recognized that "Internet Plus Nursing Service" is full of opportunities. In addition, nursing students expressed that satisfying the service needs of patients was the motive for their career choice, which highlighted the professional spirit and responsibility of young nurses, and aligned with the vision of "Internet Plus Nursing Service", making use of Internet technology to effectively expand, extend, and operate a variety of medical resources.…”
Section: Discussionmentioning
confidence: 99%
“…Nursing Service" in their spare time, thereby enhancing their personal value. [5][6][7] Nursing students recognized that "Internet Plus Nursing Service" is full of opportunities. In addition, nursing students expressed that satisfying the service needs of patients was the motive for their career choice, which highlighted the professional spirit and responsibility of young nurses, and aligned with the vision of "Internet Plus Nursing Service", making use of Internet technology to effectively expand, extend, and operate a variety of medical resources.…”
Section: Discussionmentioning
confidence: 99%
“…Authors of fourteen articles revealed how their initiatives were based, in part, on such documents. While those who spearhead faculty development initiatives appear to be well aware of the necessity of such documents, it is interesting that many educators may not have the same awareness (Boscart, McCleary, Huson, Sheiban, & Harvey, ). Nurse leaders in education, administration and research must collaborate to ensure such frameworks are embedded in nursing curricula to raise their profile with nurse educators (Negrin & Dahlke, ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, nurses could increase their income by making use of "Internet plus Nursing Service" in their spare time, thereby enhancing their personal value. [5][6][7] However, about one third of nursing students still held a neutral or integrity. It should also encourage them to keep good psychological as well as physical qualities and enhance their ability to cope with stress and frustration.…”
Section: Related Data Of Nursing Students Participating In the Surveymentioning
confidence: 99%